Biological Investigations of the Whole Plant of Argemone mexicana (L.) - Chaity, Farjana Rahman; Rashid, Mohammad A; Rahman, Mohammad Sharifur (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Abstract not available Dhaka Univ. J. Pharm. Sci. 20(1): 135-138, 2021 (June)